Reply - Cotovio, Gonçalo (2021)
Funding Information: GC was funded by Funda??o para a Ci?ncia e Tecnologia (FCT; Portugal) through a PhD Scholarship (SFRH/BD/130210/2017). AJO-M was funded by FCT (Portugal) through a Junior Research and Career Development Award from the Harvard Medical School ? Portugal Program (HMSP-ICJ/0020/2011). GC and AJO-M were supported by grant PTDC/MED-NEU/31331/2017, and AJO-M by grant PTDC/MED-NEU/30302/2017, funded by national funds from FCT/MCTES and co-funded by FEDER, under the Partnership Agreement Lisboa 2020 - Programa Operacional Regional de Lisboa. The content of this study is solely the responsibility of the authors and does not necessarily represent the official views of the Funda??o para a Ci?ncia e Tecnologia, Harvard University or its affiliated academic health care centers. Funding Information: GC was funded by Fundação para a Ciência e Tecnologia (FCT; Portugal) through a PhD Scholarship ( SFRH/BD/130210/2017 ). AJO-M was funded by FCT (Portugal) through a Junior Research and Career Development Award from the Harvard Medical School – Portugal Program ( HMSP-ICJ/0020/2011 ). GC and AJO-M were supported by grant PTDC/MED-NEU/31331/2017, and AJO-M by grant PTDC/MED-NEU/30302/2017, funded by national funds from FCT/MCTES and co-funded by FEDER , under the Partnership Agreement Lisboa 2020 - Programa Operacional Regional de Lisboa. The content of this study is solely the responsibility of the authors and does not necessarily represent the official views of the Fundação para a Ciência e Tecnologia, Harvard University or its affiliated academic health care centers. Funding Information: AJO-M was national coordinator for Portugal of a non-interventional study (EDMS-ERI-143085581, 4.0) to characterize a Treatment-Resistant Depression Cohort in Europe, sponsored by Janssen-Cilag, Ltd (2019–2020), is recipient of a grant from Schuhfried GmBH for norming and validation of cognitive tests, and is national coordinator for Portugal of trials of psilocybin therapy for treatment-resistant depression, sponsored by Compass Pathways, Ltd (EudraCT number 2017-003288-36 and 2020-001348-25), and of esketamine for treatment-resistant depression, sponsored by Janssen-Cilag, Ltd (EudraCT NUMBER: 2019-002992-33). AP-L is a co-founder of Linus Health and TI Solutions AG; serves on the scientific advisory boards for Starlab Neuroscience, Magstim Inc., Radiant Hearts, and MedRhythms; and is listed as an inventor on several issued and pending patents on the real-time integration of noninvasive brain stimulation with electroencephalography and magnetic resonance imaging. None of the aforementioned agencies or companies had a role in the design and conduct of the study, in the collection, management, analysis, and interpretation of the data, in the preparation, review, or approval of the manuscript, nor in the decision to submit the manuscript for publication. The remaining authors have declared that they have no potential conflicts of interest involving this work, including relevant financial activities outside the submitted work and any other relationships or activities that readers could perceive to have influenced, or that give the appearance of potentially influencing what is written.